Approaching the Figure of the Agroinfluencer in Spain: Definition, Typology, and Identities - Verón Lassa, José Juan; Zurutuza-Muñoz, Cristina; López-Miguel, Beatriz (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Rural depopulation, new political formations, and farmer protests have thrust rural issues into the public discourse. Within this context, the agroinfluencer has emerged as a noteworthy figure capturing media attention. This research explores the concept of agroinfluencers in Spain, outlines a typology, and analyzes the novel rural identities they project. Using a representative sample and a mixed-method approach, the study unveils a distinct profile, diverse approaches, and thematic variations. The findings open avenues for further research into rural communication and its emerging identities in the digital era.